Successful Social Media Advertising Activities For Micro, Small And Medium Enterprises - Joko Suryono; Nuryani Tri Rahayu; Purwani Indri Astuti; Nunun Tri Widarwati (MediaTor (Jurnal Komunikasi), 2020)
In Indonesia, MSMEs are a business group that is a mainstay of economic activity that is able to support most of its citizens. Economic development in Indonesia depends on the development and improvement of the capacity of MSMEs. MSMEs will be helped by improving their marketing performance through social media advertising. The use of social media advertising will create easy, cheap and fast access. Social media advertising can be used by companies to distribute advertisements and create awareness for customers. The research method in this research uses descriptive qualitative method. Data collection techniques use in-depth interviews with SMEs, library research, and focus group discussions involving advertising experts, academics, and social media experts. The data source in this study is MSMEs, advertising practitioners, communication science academics. Data analysis is carried out inductively and interactive analysis methods. The results of this study are 1) successful social media to advertise for MSMEs are websites, blogs, google, youtube, whatsapp, facebook, instagram 2) Advertising content on social media must pay attention to ad photography, watermarks, simple videos, videos as much as possible, professional videos, use of keywords, use of endorsements and testimonials 3) Awareness, consumer considerations in making purchases occur in a social media ecosystem that is interrelated and interact with each other.